2018
DOI: 10.1080/14397595.2018.1500437
|View full text |Cite
|
Sign up to set email alerts
|

2017 Clinical practice guidelines of the Japan Research Committee of the Ministry of Health, Labour, and Welfare for Intractable Vasculitis for the management of ANCA-associated vasculitis

Abstract: The revised CPG has demonstrated evidence-based treatment recommendations for AAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…In Japan, Hirayama et al reported that the 1‐year survival rate was 56.2% and the 5‐year survival rate was 41.5% in 175 DAH patients with rapidly progressive glomerulonephritis, where 50 of the 175 patients received PLEX therapy . Several studies reported the effectiveness of PLEX in DAH patients with AAV , and clinical guidelines have recommended PLEX for this population . Although the 1‐year survival in our study was only 26%, one likely reason is that very few patients (20%) received PLEX therapy.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In Japan, Hirayama et al reported that the 1‐year survival rate was 56.2% and the 5‐year survival rate was 41.5% in 175 DAH patients with rapidly progressive glomerulonephritis, where 50 of the 175 patients received PLEX therapy . Several studies reported the effectiveness of PLEX in DAH patients with AAV , and clinical guidelines have recommended PLEX for this population . Although the 1‐year survival in our study was only 26%, one likely reason is that very few patients (20%) received PLEX therapy.…”
Section: Discussionmentioning
confidence: 52%
“…Gallagher (19). Several studies reported the effectiveness of PLEX in DAH patients with AAV (20-28), and clinical guidelines have recommended PLEX for this population (7)(8)(9). Although the 1-year survival in our study was only 26%, one likely reason is that very few patients (20%) received PLEX therapy.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…AAV develops in patients with unique genetic backgrounds, and is classified into three types: microscopic polyangiitis (MPA), granulomatosis with polyangiitis (GPA), and eosinophilic granulomatosis with polyangiitis (EGPA) . Prognosis in patients with AAV has recently been improved by remission‐induction treatment using immunosuppressive agents such as cyclophosphamide and high‐dose corticosteroids (CS) . However, it has been reported that patients with AAV have significantly higher mortality than the general population, with the most common cause of death being infection .…”
Section: Introductionmentioning
confidence: 99%
“…© 2019 International Society for Apheresis, Japanese Society for Apheresis, and Japanese Society for Dialysis Therapy Ther Apher Dial, Vol. 23, No 3,. 2019 Plasma Exchange in AAV…”
mentioning
confidence: 99%